STRATEGI PENANAMAN NILAI-NILAI PENDIDIKAN ISLAM PADA PESERTA DIDIK - Raden Ahmad Muhajir Ansori (JURNAL PUSAKA, 2017)
Religious education is fundamental, particularly moral part to be taught in early process of it. Morality is the key to be smart intellectually, spiritually and emotionally. It is the responsibility of parents, teachers, and community to provide Islamic values for the students. For that, there must be a strategy in delivering these values. Some strategies that can be done to deliver religious values are (1) example or model, (2) habituation, (3) advice, and (4) punishment. Keywords: Strategy, Religious, Values